Declining fertility in Japan: Its mechanisms and policy responses - Rikiya Matsukura; Robert D. Retherford; Naohiro Ogawa (Asia-Pacific Population Journal, 2007)
Global population growth has been slowing down over the past few decades primarily because of the almost universal reduction in fertility. From 1970 to 1975, the number of countries with below-replacement fertility was 19, increasing to 65 by the period from 2000 to 2005. The overwhelming majority of those low-fertility countries are in the developed regions. However, the number of countries in the developing regions with below-replacement fertility has been increasing substantially over the past three decades, reaching 19 in the recent past. The number of countries with lowest-low fertility, being those with a total fertility rate (TFR) below 1.3, has grown from 0 to 17 during the same period.